2019
DOI: 10.1182/blood-2019-124377
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax and Ibrutinib for Patients with Relapsed/Refractory Chronic Lymphocytic Leukemia (R/R CLL) - 15-Month Safety, Response and MRD Evaluation: Third Interim Analysis from the Phase II Vision HO141 Trial

Abstract: Background: Novel targeted treatment options with fixed or minimal residual disease (MRD) guided duration are warranted for patients with R/R CLL. Post-treatment MRD has proven to predict outcome in patients receiving chemo-immunotherapy (CIT). With the BTK inhibitor ibrutinib as a single agent, rarely undetectable MRD (uMRD) is seen despite high long-term efficacy. The Bcl-2 inhibitor venetoclax + CD-20 targeting antibody results in a significant proportion of patients with uMRD; early data indicating correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…10,12,14,15 Recent clinical studies with ibrutinib plus venetoclax demonstrated high uMRD rates in both PB and BM in patients with CLL or SLL. [16][17][18][19][20] With time-limited therapies, uMRD is an important end point that appears predictive of durable efficacy outcomes. In patients treated with chemoimmunotherapy, such as fludarabine, cyclophosphamide, and rituximab (FCR), uMRD status correlated with longer PFS and OS, regardless of depth of clinical response per International Workshop on CLL (iwCLL) criteria.…”
Section: Introductionmentioning
confidence: 99%
“…10,12,14,15 Recent clinical studies with ibrutinib plus venetoclax demonstrated high uMRD rates in both PB and BM in patients with CLL or SLL. [16][17][18][19][20] With time-limited therapies, uMRD is an important end point that appears predictive of durable efficacy outcomes. In patients treated with chemoimmunotherapy, such as fludarabine, cyclophosphamide, and rituximab (FCR), uMRD status correlated with longer PFS and OS, regardless of depth of clinical response per International Workshop on CLL (iwCLL) criteria.…”
Section: Introductionmentioning
confidence: 99%
“…[233] (ibrutinib- Niemann et al . [234] VISION/HOVON Thompson et al . [235] (ibrutinibvenetoclax) deep remissions for the majority of patients (PB uMRD in 62% and 76%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The OR rate was 96%, and 67% of the patients achieved CR/CRi after six cycles of combination therapy. The rate of undetectable MRD in blood was 29% after six cycles and 47% at the end of nine cycles 83 .…”
Section: Ibrutinib Combinationsmentioning
confidence: 92%